Medial UKA: Favorable Mid-Term Results in Middle-Aged Patients - Dalury, David; Kelley, Todd C.; Adams, Mary Jo (The Journal of Knee Surgery, 2013)
In middle-aged patients with knee arthritis, surgical treatment options include arthroscopic procedures, osteotomies, and unicompartmental and total knee arthroplasty. Unicompartmental knee osteoarthrosis is particularly challenging and controversial in such patients. From December 2001 through October 2005, we treated 32 consecutive middle-aged patients (46 to 59 years old) with 40 medial unicompartmental knee arthroplasties. Three patients were lost to follow-up, leaving 29 for our study. There were two reoperations: one for loosening at 3 years, and one for disease progression at 5 years. Implant survival was modeled using Kaplan–Meier survival function with observations censored if lost to follow-up. At the 6-year survivorship in this group, the overall implant survival rate was 94.1% (95% CI, 78.3–98.5). Knee Society scores had improved significantly (p < 0.001). There were no other instances of osteolysis or radiographic failure. We concluded that, at mid-term follow-up, unicompartmental knee arthroplasty provided satisfactory results for this challenging population.
Keywords: unicondylar; unicompartmental; middle age; arthroplasty; knee